2007
DOI: 10.1016/j.ijpara.2006.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a species complex within the food-borne trematode Opisthorchis viverrini and possible co-evolution with their first intermediate hosts

Abstract: The food-borne trematodes, Opisthorchis viverrini, O. felineus and Clonorchis sinensis, have long been recognized as the cause of major human health problems, with an estimated 40 million infected persons. Of the three species of liver fluke, only O. viverrini is classified as a type 1 carcinogen because of its role as an initiator of chronic inflammation and the subsequent development of cholangiocarcinoma. At present, there are no techniques for the early diagnosis of cholangiocarcinoma and it is fatal for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
94
4
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 91 publications
(109 citation statements)
references
References 17 publications
10
94
4
1
Order By: Relevance
“…The snail collections were performed monthly in the same rice paddy field with an area of 1,534 m 2 in Phang Khon district, Sakon Nakhon Province, northeast Thailand, which is a known endemic area of O. viverrini s.l. 2 In addition to rain water, the area is irrigated with water from the Nam Un Dam through a network of irrigation canals. Consequently, irrigated water is available particularly in the dry season, allowing the planting two crops of rice per year.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The snail collections were performed monthly in the same rice paddy field with an area of 1,534 m 2 in Phang Khon district, Sakon Nakhon Province, northeast Thailand, which is a known endemic area of O. viverrini s.l. 2 In addition to rain water, the area is irrigated with water from the Nam Un Dam through a network of irrigation canals. Consequently, irrigated water is available particularly in the dry season, allowing the planting two crops of rice per year.…”
Section: Methodsmentioning
confidence: 99%
“…1 Evidence from various sources indicates that O. viverrini represents a species complex. 2,3 Human infection with O. viverrini s.l. is contracted by the consumption of raw or partially cooked fish, and chronic infection leads to hepatobiliary diseases and potentially to bile duct cancer (cholangiocarcinoma [CCA]).…”
Section: Introductionmentioning
confidence: 99%
“…In northeast Thailand, O. viverrini is a major medical problem with prevalences commonly reaching 30 -80% or more in rural populations (Saowakontha et al 1993;Sripa et al 2011;. A similarly high prevalence (60.7 -86.2%) of O. viverrini infection also occurs in Lao PDR (Kobayashi et al 2000;Sayasone et al 2009) Multilocus enzyme electrophoresis (MEE) analyses by Saijuntha et al (2007) and Kiatsopit et al (2011) found that O. viverrini is a species complex, potentially consisting of genetically very distinct but morphologically similar (hence cryptic) species which are associated with specific wetlands in Thailand and Lao PDR. Additionally, independent biological evidence has revealed significant differences in body size, fecundity and infectivity of O. viverrini that occur in different wetlands, namely the Chi and Songkram in Thailand and the Nam Ngum in Lao PDR.…”
Section: Introductionmentioning
confidence: 99%
“…From this biological evidence, in conjunction with molecular genetic data, Laoprom et al (2009) suggested that O. viverrini from the Songkram wetland (Sakon Nakhon and Nakhon Phanom) is a morphologically, genetically, and biologically distinct species. Furthermore, Saijuntha et al (2007) and Kiatsopit et al (2013) have shown that the first intermediate snail host, Bithynia siamensis goniomphalos also represents a species complex consisting of cryptic species that occur in the same wetlands as the cryptic species of O. viverrini in Thailand and Lao PDR.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, when multilocus enzyme electrophoresis was used to analyze genetic variation of O. viverrini from different geographical areas in Thailand and Lao PDR, high diversity between the isolates from different localities was observed. Thus, the authors speculated that O. viverrini did not represent a single species but rather comprised two cryptic species [54]. Unfortunately, no extensive research on the population genetics of C. sinensis has been published to date.…”
Section: Introductionmentioning
confidence: 99%